An Overview of Health-Promoting Compounds of Broccoli (Brassica Oleracea Var. Italica) and the Effect of Processing - Reyes-Salinas, A; Mahn-Osses, A (2012)
Broccoli offers many heath-promoting properties owing to its content of antioxidant and anticarcinogenic compounds. The concentration and bioavailability of polyphenols, glucosinolates, sulforaphane and selenium depend on plant biochemistry, cultivation strategy and type of processing. In this article, the main biochemical properties of broccoli are reviewed regarding their health-promoting effects. Additionally, the way these properties are affected by processing is discussed. Steaming and drying result in an apparent increment of sulforaphane content as well as antioxidant activity, most likely due to an increase of the extractability of antioxidants and sulforaphane. Freezing and boiling diminish polyphenols concentration, mainly due to volatilization and leaching into the cooking water. In view of these results, the optimization of broccoli processing in order to maximize the content of bioactive compounds should be possible. The effect of processing on selenium compounds has been poorly studied so far, and therefore this topic should be investigated in the future. Finally, the effect of operating conditions in different drying processes on the content of bioactive compounds in broccoli should be investigated in a greater depth. © 2011, SAGE Publications. All rights reserved.